Pengaruh Game Online Free Fire terhadap Perilaku Ibadah Sholat Anak-Anak Madrasah Kelurahan Malabar - Muhammad Faisal Alamul Huda; Rodliyah Khuza’i; Parihat Kamil (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. The activity of playing online games has seen a significant increase in recent years, parallel to the rapid development of technology. Online games continue to evolve with increasingly sophisticated features. This research aims to identify the extent of the influence of playing online games on the behavior of adolescent prayer practices. The study employs a quantitative method, where data is analyzed using statistics with the assistance of the SPSS 23 data processing application. The research population includes all Islamic boarding schools in Cipaera, Malabar Village. Considering the large population, the researcher selected a sample from the Muslimin Islamic boarding school in Cipaera, Malabar Village. Data collection methods involve questionnaires, observations, interviews, and documentation. Data analysis techniques include quantitative descriptive analysis, correlation analysis, simple linear regression analysis, coefficient of determination, and hypothesis testing. Data is analyzed using descriptive analytical methods. The research findings indicate that the use of online games, particularly Free Fire, has a significant impact on the behavior of prayer practices among students of Islamic boarding schools in Malabar Village. As much as 80.2% of prayer behavior is influenced by the intensity of online gaming. This influence is negative, causing students to tend not to perform prayers on time, prioritize playing online games over religious obligations, feel lazy in performing prayers, lack awareness of prayer responsibilities, and neglect the quality of prayer performance. This research provides important insights into the impact of playing online games on the religious aspect of adolescents. The implications of these findings can serve as a basis for the development of educational strategies or interventions aimed at guiding adolescents in balancing online gaming activities and fulfilling religious duties. Furthermore, future research could explore additional factors that may affect prayer behavior in a broader population. Abstrak. Aktivitas bermain game online dalam beberapa tahun ini terus meningkat. Game online semakin berkembang seiring dengan perkembangan teknologi yang semakin canggih. Penelitian ini bertujuan untuk mengetahui besarnya pengaruh bermain game online terhadap perilaku pelaksanaan ibadah shalat remaja. Penelitian ini menggunakan metode penelitian kuantitatif, dimana analisis datanya diproses dengan menggunakan statistika dengan dibantu aplikasi pengolahan data yaitu SPSS 23. Populasi yang diambil dalam penelitian ini adalah seluruh madrasah diniyah di Cipaera kelurahan Malabar. Melihat banyaknya populasi maka peneliti mengambil sampel di madrasah Muslimin Cipaera kelurahan Malabar. Metode pengumpulan data adalah kuisioner, observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan adalah deskriptif kuantitatif meliputi analisis korelasi, analisis regresi linear sederhana, koefisien determinasi dan uji hipotesis. Data dianalisa dengan metode deskriptif analisis. Hasil penelitian menunjukkan bahwa penggunaan game online sangat berpengaruh terhadap perilaku ibadah sholat anak-anak madrasah diniyah kelurahan Malabar. Pengaruh Perhitungan pada penelitian ini menunjukan bahwa penggunaan game online free fire yang tinggi dapat mempengaruhi terhadap ibadah sholat anak-anak madrasah di kelurahan malabar sebesar 80,2%. Pengaruh yang ditimbulkan adalah pengaruh negatif. Bermain game online membuat anak-anak madrasah tidak melaksanakan shalat diawal waktu, lebih mendahulukan bermain game online daripada melaksanakan ibadah shalat di awal waktu, malas dalam melaksanakan ibadah shalat, tidak memiliki kesadaran untuk melaksanakan ibadah shalat terhadap kaifiah dalam pelaksanakan ibadah shalat.